Perspektif Undang-Undang Hak Cipta dan Undang-Undang ITE Terhadap Penyebarluasan Buku Elektronik - Daud, Daud (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The very rapid development of technology and science has led to new, innovative discoveries that can help make it easier for humans to live their lives. However, it is a shame that current technological developments are not balanced with public awareness of the importance of respecting other people's works by understanding intellectual concepts. The type of research used in this research is normative legal research with a qualitative research type. The problem approach used is a statutory approach. The data obtained was then analyzed qualitatively. The research methods used are data collection methods and data processing methods. The results of the research and discussion show that the regulation of electronic media in the ITE Law is not clear enough even though the two have synergized with each other in providing legal protection against copyright infringement. The form of preventive protection for authors is stated in Article 1 point 1 of the ITE Law. Apart from that, socialization, education, mediation activities were held, as well as activities to limit the number of message recipients through the forward feature on WhatsApp and the use of security technology on electronic media, better known as Digital Rights Management (DRMs). Repressive protection takes the form of providing strict sanctions as stated in Article 113 Paragraph (3) UUHC and Article 48 Paragraph (2) UU ITE if there is a complaint from the aggrieved party.